Quake'n and Shake'n...Forever! Long-Run Effects of Natural Disasters: A Case Study on the 1970 Ancash Earthquake - Germán Caruso; Sebastián Miller (Inter-American Development Bank (IDB), 2014)
This study estimates the effects of the 1970 Ancash earthquake on human capital accumulation on the affected and subsequent generation, 37 years after the shock, using the Peruvian censuses of 1993 and 2007. The main finding is that males affected by the earthquake in utero completed on average 0. 5 years less schooling while females affected by the earthquake completed 0. 8 years less schooling. Surprisingly, those whose mothers were affected at birth by the earthquake have 0. 4 less years of education, while those whose fathers were affected by the earthquake at birth have no effects on their education. The evaluation of other outcomes also suggests that the level of welfare of the affected individuals has been negatively impacted in the long run. The present investigation supports previous literature on shocks in early childhood, providing evidence of the existence of intergenerational transmission of shocks.
hdl:11319/6672
Keywords: D31; I32; C49; 330; Long-term effects; Intergenerational transmission; Natural disasters